ANALISIS KINERJA ACCOUNT REPRESENTATIVE (AR) DALAM UPAYA PENINGKATAN KEPATUHAN WAJIB PAJAK DI KPP PRATAMA MANADO - Waghe, Alter S.; Pangemanan, Sifrid; Pangerapan, Sonny (Universitas Sam Ratulangi, 2018)
Tax is a people's contribution to the state that is compelling and the benefits can not be directly felt by the community. Account representative (AR) is an employee who is appointed and designated as an Account representative (AR) in the tax service office and each Account representative (AR) has several taxpayers who must be supervised. The purpose of this study was to analyze the performance of Account Representative (AR) in an effort to increase taxpayer compliance at the KPP Pratama Manado. The analytical method used in this study is descriptive. The results of this study indicate that the Account representative (AR) performance for 2014-2016 has been going well even though in 2014 and 2015 seen from the indicators of proposed special examinations and indicators of visit visit performance Account representative (AR) has not reached the target, but in 2016 already achieve the target and for the level of taxpayer compliance in KPP Pratama Manado in 2014-2016 is still low but each year has increased compliance. Account representative (AR) further enhances performance in efforts to increase compliance by continuously exploring the potential of tax revenue and increasing socialization to taxpayers.Keywords: performance, Account representative (AR), taxpayer compliance